Occurence and spreading of box tree moth (Cydalima perspectalis Walker 1859) on the North-East region of Great Hungarian Plain - Szanyi, Szabolcs; Nagy, Antal; Csabai, Judit; Molnár, Attila; Molnár, Béla; Kárpáti, Zsolt; Tóth, Miklós; Szarukán, István (Acta Agraria Debreceniensis, 2017)
Box tree moth shows (Cydalima perspectalis) rapid spread in Europe. In Hungary it appeared first near to the western border of the country in 2011. In the eastern part of Hungary the first specimen was caught in 2015 with blacklight trap. Here we summarize its distribution in northern part of the Alföld (Great Hungarian Plain) on the basis of blacklight, pheromone and feeding attractant traps. We publish five new distribution data from northern part (4 from Hungary, 1 from Transcarpathia) and two from southern part of the Alföld. Beyond that the flight of three generations was observed both in the year 2015 and 2016.